Answer:
![y=-(2)/(3) x+4](https://img.qammunity.org/2023/formulas/mathematics/high-school/9yuc3d3btr8ouy44glcla3j6xwkxevevfl.png)
Explanation:
move the variable to the right(-2x) and change the sign(2x now) -3y=-12+2x then change the signs (-3y is 3y , -12 is 12 and then 2x becomes -2x again) then divide both sides of the equation by 3 so 12÷3=4 and -2x÷3=
then you're going to use the commutative property to reorder the terms . so your answer is
![y=-(2)/(3) x+4](https://img.qammunity.org/2023/formulas/mathematics/high-school/9yuc3d3btr8ouy44glcla3j6xwkxevevfl.png)